Professionalism, competency and financial reporting quality: a perception of director of finance in a changing public sector reporting standard - Maruf Mustapha; Ku Nor Izah Ku Ismail; Halima Nasibah Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2019)
The Financial Reporting Quality (FRQ) refers to better information dissemination across different users. It remains a prevalent factor for organizations’ performance and survival. The public sector in many countries, have witnessed considerable changes in the past decades. The prominent one being the International Public Sector Accounting Standards (IPSAS) for the public sector entities. Drawing on contingency and institutional theories, this study examine the perception of directors of finance regarding the effects of professionalism on the relationship between staff competency and FRQ under a new accounting standard. Using survey research approach and self-administered questionnaire, data were gathered from 118 directors of finance representing local governments of four States in the north-west geographical zone of Nigeria. The Partial Least Squares Structural Equation Modeling (PLS-SEM) revealed a significant positive relation between staff competence and FRQ. Conversely, no significant effect was found in the interaction of professionalism on the model. The study implication was discussed in the context of Nigeria.